Dissection of Chemical Composition and Associated Gene Expression in the Pigment-Deficient Tea Cultivar ‘Xiaoxueya’ Reveals an Albino Phenotype and Metabolite Formation - Li, Na-Na; Lu, Jian-Liang; Li, Qing-Sheng; Zheng, Xin-Qiang; Wang, Xin-Chao; Wang, Lu; Wang, Yu-Chun; Ding, Chang-Qing; Liang, Yue-Rong; Yang, Ya-Jun (Frontiers in Plant Science, 2019)
The tea cultivar ‘Xiaoxueya’, a temperature-sensitive albino mutant, is a rare tea germplasm because of its highly enriched amino acid content and brisk flavour. In comparison with green leaf tissues of ‘Xiaoxueya’, albino leaves show significant deficiency in chlorophylls and carotenoids and severely disrupted chloroplasts. Furthermore, the accumulation of quality-related secondary metabolites is altered in ‘Xiaoxueya’ albino leaf, with significantly increased contents of total amino acids, theanine and glutamic acid and significantly decreased contents of alkaloids, catechins and polyphenols. To uncover the molecular mechanisms underlying albinism and quality-related constituent variation in ‘Xiaoxueya’ leaves, expression profiles of pivotal genes involved in the biosynthetic pathways of pigments, caffeine, theanine and catechins were investigated by quantitative real-time PCR technology. The results revealed that suppressed expression of the chloroplast-localized 1-deoxy-D-xylulose-5-phosphate synthase genes DXS1 and DXS2 involved in the 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway and protochlorophyllide oxidoreductase genes POR1 and POR2 involved in the chlorophyll biosynthetic pathway is responsible for the pigment deficiency in ‘Xiaoxueya’ albino leaf. Additionally, the low expression of the tea caffeine synthase gene (TCS) involved in caffeine biosynthesis and the chalcone synthase genes CHS1, CHS2 and CHS3, the chalcone isomerase gene CHI, the flavonoid 3’,5’-hydroxylase genes F3’5’H1 and F3’5’H2, and the anthocyanidin reductase genes ANR1 and ANR2 involved in the flavonoid pathway is related to the reduction in alkaloid and catechin levels in ‘Xiaoxueya’ albino leaves.